1987
DOI: 10.3109/02656738709140415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermochemotherapy on the development of spontaneous lung metastases

Abstract: Effect of local hyperthermia given alone or in combination with cyclophosphamide and/or hyperglycaemia on the development of lung metastasis was studied using a non-immunogenic mouse fibrosarcoma, FSa-II. Incidence of lung metastasis was dependent upon the tumour size, and was increased when tumour-bearing mice were restrained in animal holders which were used for heat-treatment of animal tumours. The frequency of the metastatic spread was decreased following local hyperthermia at 41.5 degrees and 45.5 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Cells with increased baseline HSP levels exhibit greater thermoresistance and are afforded additional protection from protein loss [45]. Increased expression of HSPs in surviving tumour cells at the margins of thermal ablated tumours may lead to the development of more malignant and heat resistant tumour strains [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Cells with increased baseline HSP levels exhibit greater thermoresistance and are afforded additional protection from protein loss [45]. Increased expression of HSPs in surviving tumour cells at the margins of thermal ablated tumours may lead to the development of more malignant and heat resistant tumour strains [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Cells with increased baseline HSP levels are afforded added protection from protein loss and exhibit greater thermoresistance [93]. Increased expression of these proteins in surviving tumor cells following focal hyperthermia may lead to the progressive development of more malignant and heat resistant tumor strains [94].…”
Section: Influence Of Tumor Biology On Direct Injurymentioning
confidence: 99%
“…Augmented effects of various cytotoxic agents by hyperthermia have been found by many authors in numerous tumor sys tems [19][20][21][22][23]. Several recent studies have shown an increased antineoplastic activity of cytotoxic agents in conjunction with calcium channel blockers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms of the antineoplastic effect of hyperthermia is an action on the cell membrane [10][11][12][13][14][15][16][17][18]. Hy perthermic treatment has been found to enhance the inhibitory effects of various cytotoxic agents on different tumors [19][20][21][22][23]. Verapamil acts on the cell mem brane as a calcium channel blocker [24][25][26], Increased activity of antitumoral cytotoxic agents in the presence of calcium antagonists has been reported [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%